Type II anhydrite premixed concrete and preparation method thereof

By calcining and modifying phosphogypsum into type II anhydrous gypsum, combined with raw materials such as semi-water gypsum and special admixtures, an efficient type II anhydrous gypsum premix concrete was prepared, which solved the impact of impurities in phosphogypsum and the absence of non-existence. The problem of lack of strength of water gypsum has achieved high strength, wear resistance and dissolution resistance in the early stage.

CN119430840APending Publication Date: 2025-02-14GUIZHOU KAILIN INT TRADING CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411423944.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the presence of impurities in phosphogypsum affects the hydration hardening and cracking of gypsum, and the anhydrous gypsum itself lacks strength and requires admixtures to exert its application range. At the same time, the disadvantages of gypsum fear of water and softening when exposed to water restrict the development of gypsum building materials products.

Method used

A type II anhydrous gypsum is prepared by calcining and modifying it into Type II anhydrous gypsum, combining hemihydrous gypsum, calcium silicate powder, gravel, mountain sand and special admixtures. The admixture consists of a retarder, calcium formate, carboxylic acid reducing agent, etc., and is used to retarder, reduce water usage, improve compressive strength and ease, and resist dissolution.

Benefits of technology

It realizes efficient utilization of phosphogypsum, controllable settling time, high early strength, good wear and dissolution resistance, compressive strength between 7~10MPa, and can reach 25~30MPa after 7 days of natural curing, suitable for floor or Pavement construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081623050000071
    Figure BDA0005081623050000071
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete, and particularly relates to II-type anhydrous gypsum premixed concrete and a preparation method thereof. The II-type anhydrous gypsum premixed concrete is prepared from the following raw materials in parts by weight: 25 to 28 parts of II anhydrous gypsum, 5 to 7 parts of semi-hydrated gypsum powder, 1.2 to 1.6 parts of calcium silicate, 0.2 to 0.5 part of an additive, 7 to 11 parts of water, 29 to 35 parts of gravel and 28 to 32 parts of mountain sand. The use amount of phosphogypsum is up to 95% or above, and the setting time is controllable and easy to adjust. The coating has the properties of high early strength, wear resistance, corrosion resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of concrete technology, and in particular relates to a type II anhydrous gypsum ready-mixed concrete and a preparation method thereof. Background Art

[0002] China's phosphogypsum resource utilization technology has basically matured, and some key common technologies have been broken through and applied, mainly in the primary utilization channels such as cement retarders and various building materials products. In addition, there are a small amount of phosphogypsum soil conditioners, phosphogypsum sulfuric acid and other application channels, as well as gypsum-based self-leveling, plaster mortar, roadbed fillers, polymer fillers and other products that are widely promoted and applied. With the formal proposal of the "dual carbon" goal, using phosphogypsum as a raw material to produce a low-carbon building material product has become the future trend of phosphogypsum recycling.

[0003] On the one hand, the presence of impurities in phosphogypsum (such as soluble phosphorus, eutectic phosphorus, soluble fluorine and organic matter, etc.) affects the hydration, hardening and cracking of gypsum, thereby affecting the performance of gypsum products. Therefore, phosphogypsum must be treated with impurities. The phosphogypsum after impurities removal can be made into anhydrous gypsum by high-temperature calcination and dehydration. However, since anhydrous gypsum itself has no strength, it needs to be added with activators, waterproof and wear-resistant agents to maximize its application range. The materials prepared by this method can be widely used in concrete construction and other building materials. On the other hand, gypsum itself has the disadvantages of being afraid of water and softening when exposed to water, which restricts the development of gypsum building materials. However, at present, by adopting the scientific and reasonable dosage of admixtures, crushed stone, sand and type II anhydrous gypsum, we have basically solved the problems of dissolution, cracking, softening when exposed to water.

[0004] Therefore, in order to utilize phosphogypsum more efficiently, combining phosphogypsum with concrete is one of the current key research directions. Summary of the invention

[0005] In order to solve the above technical problems existing in the prior art, the present application provides a type II anhydrous gypsum ready-mixed concrete and a preparation method thereof, which is specifically achieved through the following technical scheme:

[0006] A type II anhydrous gypsum premixed concrete is composed of the following raw materials: type II anhydrous gypsum, semi-hydrated gypsum, calcium silicate powder, crushed stone, mountain sand with a particle size less than 5 mm, admixtures and water.

[0007] Furthermore, the admixture is composed of the following raw materials in parts by weight: 4-7 parts of retarder, 1-3 parts of calcium formate, 30-35 parts of carboxylic acid reducer, 1-2 parts of rubber powder, 2-5 parts of cellulose, 2-4 parts of defoamer, 28-34 parts of calcium hydroxide, and 1-2 parts of viscosity reducer. During its preparation, each component is poured into a mixer and slowly stirred for 5-10 minutes to obtain a uniformly mixed admixture. The admixture is used in type II anhydrous gypsum concrete to slow down setting, reduce water consumption, improve concrete compressive strength and workability, and resist corrosion.

[0008] Furthermore, the type II anhydrous gypsum is a powder material obtained by calcining phosphogypsum at a temperature of 700-900°C and then grinding and modifying it in a ball mill. The powder material has a pH value of 8-12, 1% potassium sulfate is added and mixed evenly, and 50% water is stirred to form a slurry. The initial setting time is measured to be 180-240 minutes, the final setting time is 370-450 minutes, and the 24h compressive strength is 7-10MPa.

[0009] Furthermore, the semi-hydrated gypsum is obtained by calcining phosphogypsum at 150-210°C, with a 400 mesh sieving rate of 100%. Its main component is CaSO4·1 / 2H2O, wherein the content of CaSO4·1 / 2H2O is ≥75%, the content of CaSO4·2H2O is ≤5%, and the content of AⅢ anhydrous gypsum is ≤8%.

[0010] Furthermore, the gravel has a particle size of 5 to 26.5 mm.

[0011] Furthermore, the mountain sand is mountain sand with a particle size less than 5 mm.

[0012] Further, the specific weight parts of each raw material are as follows:

[0013] Ⅱ 25-28 parts of anhydrous gypsum, 5-7 parts of hemihydrate gypsum powder, 1.2-1.6 parts of calcium silicate, 0.2-0.5 parts of admixture, 7-11 parts of water, 29-35 parts of crushed stone, and 28-32 parts of mountain sand.

[0014] The method for preparing type II anhydrous gypsum ready-mixed concrete comprises the following steps:

[0015] (1) Material preparation: weigh type II anhydrous gypsum, hemihydrate gypsum, calcium silicate powder, crushed stone, mountain sand with a particle size of less than 5 mm, admixtures, water and other raw materials according to the weight ratio and pour them into the mixer of the concrete production line;

[0016] (2) Stirring and mixing: Start the mixer and stir for 3 to 5 minutes to obtain the mortar fluid of Type II anhydrous gypsum ready-mixed concrete. Open the warehouse and put it into the transfer tank truck for standby use. It can be directly transported to the designated road or ground for construction use. This concrete is mainly used for floor or road surface.

[0017] Furthermore, in step (2), the material and water can be added simultaneously in set amounts, or water can be added during stirring after the material is added.

[0018] Furthermore, in step (2), the stirring time starts when all the materials have been added.

[0019] Compared with the prior art, the technical effects created by this application are embodied in:

[0020] 1. The premixed concrete of the present invention uses phosphogypsum up to 95% or more, and the setting time is controllable and easy to adjust. It has high early strength, wear resistance, corrosion resistance and other properties; with anhydrous gypsum as the main raw material, and then adding a certain amount of domestic water, under the condition of rapid stirring in the mixer and collision with sand and gravel, the anhydrous gypsum is quickly hydrated, and in the process of hydration reaction, accompanied by tissue regulation, the molecular arrangement is changed, so that the molecular structure of phosphogypsum changes from the original chaotic arrangement of needles and sheets to a dense structure of flocculent, and the gravel is organically wrapped with sand. Thereby improving the density of the concrete after pouring, effectively preventing the entry of water molecules, thereby improving the strength and softening coefficient, and effectively enhancing wear resistance and corrosion resistance.

[0021] 2. After 7 days of natural curing, the compressive strength of the premixed concrete of the present invention can reach 25 to 30 MPa, and can be widely used in indoor and outdoor floor projects.

[0022] 3. The method of the present invention uses waste residue phosphogypsum for production, which has low production cost, short production time, easy construction, and achieves low carbon and environmental protection. DETAILED DESCRIPTION

[0023] The technical solution of the present application is further limited below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.

[0024] Example 1

[0025] A type II anhydrous gypsum premixed concrete, the raw materials include, by weight: 26.5 parts of type II anhydrous gypsum, 6.2 parts of hemihydrate gypsum powder, 1.2 parts of calcium silicate, 0.24 parts of admixture, 8.4 parts of domestic water, 30.5 parts of crushed stone with a particle size of 5 to 26.5 mm, 29.3 parts of mountain sand with a particle size of less than 5 mm, start a mixer and stir for 4 minutes;

[0026] The anhydrous gypsum is type II anhydrous gypsum powder, which is a powder material obtained by calcining phosphogypsum at a temperature of 700-900°C and then grinding and modifying it with a ball mill. The pH value of the powder material is 8-12. After adding 1% potassium sulfate and mixing evenly, it is stirred with 50% water to form a slurry. The initial setting time is measured to be 180-240 minutes, the final setting time is 370-450 minutes, and the 24h compressive strength is 7-10MPa.

[0027] The semi-hydrated gypsum is obtained by calcining phosphogypsum at 150-210°C, with a 400 mesh sieving rate of 100%. Its main component is CaSO4·1 / 2H2O, wherein the content of CaSO4·1 / 2H2O is ≥75%, the content of CaSO4·2H2O is ≤5%, and the content of AⅢ anhydrous gypsum is ≤8%. The preparation process is dihydrate phosphogypsum→feeding belt, pre-drying→calcining kiln→gas-solid separator→modified mill→bucket elevator→powder selector→finished product silo.

[0028] Example 2

[0029] A type II anhydrous gypsum premixed concrete, the raw materials include, by weight: 27.3 parts of type II anhydrous gypsum, 7 parts of hemihydrate gypsum powder, 1.3 parts of calcium silicate, 0.23 parts of admixture, 8.5 parts of domestic water, 32 parts of crushed stone with a particle size of 5 to 26.5 mm, 28 parts of mountain sand with a particle size of less than 5 mm, start a mixer and stir for 4 minutes;

[0030] The anhydrous gypsum is type II anhydrous gypsum powder, which is a powder material obtained by calcining phosphogypsum at a temperature of 700-900°C and then grinding and modifying it with a ball mill. The pH value of the powder material is 8-12. After adding 1% potassium sulfate and mixing evenly, it is stirred with 50% water to form a slurry. The initial setting time is measured to be 180-240 minutes, the final setting time is 370-450 minutes, and the 24h compressive strength is 7-10MPa.

[0031] The semi-hydrated gypsum is obtained by calcining phosphogypsum at 150-210°C, with a 400 mesh sieving rate of 100%. Its main component is CaSO4·1 / 2H2O, wherein the content of CaSO4·1 / 2H2O is ≥75%, the content of CaSO4·2H2O is ≤5%, and the content of AⅢ anhydrous gypsum is ≤8%. The preparation process is dihydrate phosphogypsum→feeding belt, pre-drying→calcining kiln→gas-solid separator→modified mill→bucket elevator→powder selector→finished product silo.

[0032] Example 3

[0033] A type II anhydrous gypsum premixed concrete, the raw materials include, by weight: 28.6 parts of type II anhydrous gypsum, 7.2 parts of hemihydrate gypsum powder, 1.4 parts of calcium silicate, 0.25 parts of admixture, 8.3 parts of domestic water, 33 parts of crushed stone with a particle size of 5 to 26.5 mm, 29 parts of mountain sand with a particle size of less than 5 mm, start a mixer and stir for 4 minutes;

[0034] The anhydrous gypsum is type II anhydrous gypsum powder, which is a powder material obtained by calcining phosphogypsum at a temperature of 700-900°C and then grinding and modifying it with a ball mill. The pH value of the powder material is 8-12. After adding 1% potassium sulfate and mixing evenly, it is stirred with 50% water to form a slurry. The initial setting time is measured to be 180-240 minutes, the final setting time is 370-450 minutes, and the 24h compressive strength is 7-10MPa.

[0035] The semi-hydrated gypsum is obtained by calcining phosphogypsum at 150-210°C, with a 400 mesh sieving rate of 100%. Its main component is CaSO4·1 / 2H2O, wherein the content of CaSO4·1 / 2H2O is ≥75%, the content of CaSO4·2H2O is ≤5%, and the content of AⅢ anhydrous gypsum is ≤8%. The preparation process is dihydrate phosphogypsum→feeding belt, pre-drying→calcining kiln→gas-solid separator→modified mill→bucket elevator→powder selector→finished product silo.

[0036] Example 4

[0037] A type II anhydrous gypsum premixed concrete, the raw materials include, by weight: 7.2 parts of type II anhydrous gypsum, 28.3 parts of hemihydrate gypsum powder, 1.4 parts of calcium silicate, 0.24 parts of admixture, 8.3 parts of domestic water, 32 parts of crushed stone with a particle size of 5 to 26.5 mm, 29.2 parts of mountain sand with a particle size of less than 5 mm, start a mixer and stir for 4 minutes;

[0038] The anhydrous gypsum is type II anhydrous gypsum powder, which is a powder material obtained by calcining phosphogypsum at a temperature of 700-900°C and then grinding and modifying it with a ball mill. The pH value of the powder material is 8-12. After adding 1% potassium sulfate and mixing evenly, it is stirred with 50% water to form a slurry. The initial setting time is measured to be 180-240 minutes, the final setting time is 370-450 minutes, and the 24h compressive strength is 7-10MPa.

[0039] The semi-hydrated gypsum is obtained by calcining phosphogypsum at 150-210°C, with a 400 mesh sieving rate of 100%. Its main component is CaSO4·1 / 2H2O, wherein the content of CaSO4·1 / 2H2O is ≥75%, the content of CaSO4·2H2O is ≤5%, and the content of AⅢ anhydrous gypsum is ≤8%. The preparation process is dihydrate phosphogypsum→feeding belt, pre-drying→calcining kiln→gas-solid separator→modified mill→bucket elevator→powder selector→finished product silo.

[0040] Example 5

[0041] A type II anhydrous gypsum premixed concrete, the raw materials include, by weight: 12 parts of type II anhydrous gypsum, 16.3 parts of hemihydrate gypsum powder, 1.4 parts of calcium silicate, 0.24 parts of admixture, 8.3 parts of domestic water, 32 parts of crushed stone with a particle size of 5 to 26.5 mm, 29.2 parts of mountain sand with a particle size of less than 5 mm, start a mixer and stir for 4 minutes;

[0042] The anhydrous gypsum is type II anhydrous gypsum powder, which is a powder material obtained by calcining phosphogypsum at a temperature of 700-900°C and then grinding and modifying it with a ball mill. The pH value of the powder material is 8-12. After adding 1% potassium sulfate and mixing evenly, it is stirred with 50% water to form a slurry. The initial setting time is measured to be 180-240 minutes, the final setting time is 370-450 minutes, and the 24h compressive strength is 7-10MPa.

[0043] The semi-hydrated gypsum is obtained by calcining phosphogypsum at 150-210°C, with a 400 mesh sieving rate of 100%. Its main component is CaSO4·1 / 2H2O, wherein the content of CaSO4·1 / 2H2O is ≥75%, the content of CaSO4·2H2O is ≤5%, and the content of AⅢ anhydrous gypsum is ≤8%. The preparation process is dihydrate phosphogypsum→feeding belt, pre-drying→calcining kiln→gas-solid separator→modified mill→bucket elevator→powder selector→finished product silo.

[0044] In order to further illustrate that the present invention can achieve the technical effect, the following experiment was conducted: a type II anhydrous gypsum premixed concrete was prepared using Examples 1 to 3 of the present application, and its compressive strength, freeze-thaw and softening coefficient were tested during the application process. At the same time, the cost required to prepare a type II anhydrous gypsum premixed concrete was recorded. The specific experimental results are shown in Table 1 below.

[0045]

[0046] In the present application, the anhydrous gypsum is mixed with the admixture to react with water to form dihydrate gypsum crystals, which are flocculent. During the mixing process, the sand and the gypsum are fully combined to form a colloid, and the colloid organically wraps the crushed stone to obtain a type II anhydrous gypsum premixed concrete. After the curing time is greater than 7, a high-density concrete with small gaps between gypsum molecules, corrosion resistance, and a softening coefficient of more than 0.8 is formed, which has certain waterproofness and wear resistance.

[0047] Finally, it should be pointed out that the above embodiments are only representative examples of the present application. Obviously, the technical solution of the present application is not limited to the above embodiments, and there may be many variations. All variations that can be directly derived or associated with the contents disclosed in the present application by a person of ordinary skill in the art should be considered as the protection scope of the present application.

Claims

1. A type II anhydrous gypsum ready-mixed concrete, characterized in that: It is composed of the following raw materials: type II anhydrous gypsum, semi-hydrated gypsum, calcium silicate powder, crushed stone, mountain sand with particle size less than 5mm, admixtures and water.

2. The type II anhydrous gypsum ready-mixed concrete according to claim 1, characterized in that: The admixture is composed of the following raw materials in parts by weight: 4-7 parts of retarder, 1-3 parts of calcium formate, 30-35 parts of carboxylic acid reducer, 1-2 parts of rubber powder, 2-5 parts of cellulose, 2-4 parts of defoamer, 28-34 parts of calcium hydroxide, and 1-2 parts of viscosity reducer.

3. The type II anhydrous gypsum ready-mixed concrete according to claim 2, characterized in that: The external additive is prepared by pouring each component into a mixer and slowly stirring for 5 to 10 minutes to obtain a uniformly mixed external additive.

4. The type II anhydrous gypsum ready-mixed concrete according to claim 1, characterized in that: The type II anhydrous gypsum is a powder material obtained by calcining phosphogypsum at a temperature of 700-900°C and then grinding and modifying it with a ball mill.

5. The type II anhydrous gypsum ready-mixed concrete according to claim 1, characterized in that: The semi-hydrated gypsum is obtained by calcining phosphogypsum at 150-210° C., and has a 400-mesh sieving rate of 100%.

6. The type II anhydrous gypsum ready-mixed concrete according to claim 5, characterized in that: The semi-hydrated gypsum mainly comprises CaSO4·1 / 2H2O, wherein the content of CaSO4·1 / 2H2O is ≥75%, the content of CaSO4·2H2O is ≤5%, and the content of AⅢ anhydrous gypsum is ≤8%.

7. The type II anhydrous gypsum ready-mixed concrete according to claim 1, characterized in that: The crushed stone has a particle size of 5 to 26.5 mm.

8. The type II anhydrous gypsum ready-mixed concrete according to claim 1, characterized in that: The mountain sand is mountain sand with a particle size less than 5 mm.

9. The type II anhydrous gypsum ready-mixed concrete according to claim 1, characterized in that: The specific weight parts of each raw material are as follows: Ⅱ 25-28 parts of anhydrous gypsum, 5-7 parts of hemihydrate gypsum powder, 1.2-1.6 parts of calcium silicate, 0.2-0.5 parts of admixture, 7-11 parts of water, 29-35 parts of crushed stone, and 28-32 parts of mountain sand.

10. The method for preparing type II anhydrous gypsum ready-mixed concrete according to claim 1, characterized in that: The steps include: (1) Material preparation: weigh type II anhydrous gypsum, hemihydrate gypsum, calcium silicate powder, crushed stone, mountain sand with a particle size of less than 5 mm, admixtures, water and other raw materials according to the weight ratio and pour them into the mixer of the concrete production line; (2) Stirring and mixing: Start the mixer and stir for 3 to 5 minutes to obtain the mortar fluid for Type II anhydrous gypsum premixed concrete. Open the tank and put it into the transport tank truck for standby use.

Citation Information

Cited By

  • Gypsum concrete based on high-temperature gypsum-based cementing material and preparation method thereof

    CN120309299A